2002
DOI: 10.1074/jbc.m200889200
|View full text |Cite
|
Sign up to set email alerts
|

A Point Mutation That Confers Constitutive Activity to CXCR4 Reveals That T140 Is an Inverse Agonist and That AMD3100 and ALX40-4C Are Weak Partial Agonists

Abstract: CXCR4 is a G protein-coupled receptor for stromalderived factor 1 (SDF-1) that plays a critical role in leukocyte trafficking, metastasis of mammary carcinoma, and human immunodeficiency virus type-1 infection. To elucidate the mechanism for CXCR4 activation, a constitutively active mutant (CAM) was derived by coupling the receptor to the pheromone response pathway in yeast. Conversion of Asn-119 to Ser or Ala, but not Asp or Lys, conferred autonomous CXCR4 signaling in yeast and mammalian cells. SDF-1 induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
229
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 236 publications
(249 citation statements)
references
References 38 publications
19
229
1
Order By: Relevance
“…14 Comparative studies between T-140 and AMD3100 found that each of these agents inhibited CXCR4 through different mechanisms. 11,12,14 Analysis of antagonists revealed that exposure to AMD3100 induced G protein activation by CXCR4, whereas T-140 decreased autonomous signaling. 12 Therefore, AMD3100 was defined to have a weak partial agonist activity, whereas T-140 functions as an inverse agonist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Comparative studies between T-140 and AMD3100 found that each of these agents inhibited CXCR4 through different mechanisms. 11,12,14 Analysis of antagonists revealed that exposure to AMD3100 induced G protein activation by CXCR4, whereas T-140 decreased autonomous signaling. 12 Therefore, AMD3100 was defined to have a weak partial agonist activity, whereas T-140 functions as an inverse agonist.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,14 Analysis of antagonists revealed that exposure to AMD3100 induced G protein activation by CXCR4, whereas T-140 decreased autonomous signaling. 12 Therefore, AMD3100 was defined to have a weak partial agonist activity, whereas T-140 functions as an inverse agonist. In our current work, we found that SDF-1a at high levels, as well as T140, but not AMD3100, similarly affect the proliferation and differentiation of progenitors, granulocytes and erythroblasts when co-cultured with stromal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…71 Also, in a series of experiments to elucidate the mechanism of CXCR4 signaling, it was noticed that T140 decreased autonomous CXCR4 signaling in CXCR4 wild-type or constitutively active CXCR4 mutants, characterizing T140 as an inverse CXCR4 agonist, whereas AMD3100 and ALX40-4C displayed partial agonist activity in this study. 72 Clinical trials will help to determine whether this characteristic of CXCR4 peptide antagonists correlates with a profile of activities and/or side effects that is distinct from AMD3100.…”
Section: Small Peptide Antagonist Of Cxcr4mentioning
confidence: 99%
“…AMD3100 was withdrawn from clinical trials in patients with HIV-1 infections because of cardiac toxicity. 2 The mechanism of antagonist action has been determined using human CXCR4 mutants with constitutive activity derived in yeast strains expressing the receptor functionally coupled to the pheromone response pathway (10). AMD3100 and ALX40-4C demonstrated weak partial agonist activity (10).…”
mentioning
confidence: 99%